ضوابط تدبر القرآن بين عبد الرحمن حبنكة الميداني، وأبو الحسن علي الندوي، وطه جابر العلواني: دراسة مقارنة (Al-Qamar, 2025)
The Holy Quran is a message of civilization, a book of religion, and a way of life. A nation can only progress and live in harmony with other civilizations and nations by adhering to it. Otherwise, ignorance and backwardness will accompany it, along with the loss of its identity, the extinction of its civilization, and the loss of its religion.The question that arises is the best methodology for dealing with the Quran. The methodology outlined by the Quran for dealing with it is the methodology of contemplating its verses.Our esteemed interpreters from the early generations laid down various methodologies for dealing with the Quran through their contemplation, in light of the challenges of their times and regions. This enables us to benefit from the teachings and guidance of the Quran in the modern era. Contemplation of the Quran is an ongoing process, adapting to the needs of each era and society, to connect our nation to the strong bond of Allah and derive solutions for contemporary issues and face current challenges.Therefore, the focus of this study is on some of the prominent contemporary interpreters through their books in Quranic studies and contemplation. These figures are: Abdul Rahman Habnaka al-Midani (died: 1978), Abu al-Hasan Ali al-Nadwi (died: 1999), and Taha Jaber al-Alwani (died: 2016).The study aims to examine the proposed methodologies of contemplation among them and extract the key features.
Keywords: Contemplating the Quran; Guidelines; Abd al-Rahmān Ḥabnakah al-Mīdānī; Abū al-Ḥasan ʿAlī al-Nadwī; Ṭāhā Jābir al-ʿAlwānī